Involvement of physicians in management: A literature review - SLIM, Hiba (Proche-Orient Études en management, 2022)
The aim of this article is to shed light on what has been previously explored by researchers about the hybridization of physicians through involving them in management, especially given the complexity of healthcare organizations. This makes it possible to identify the approaches and perspectives, which have been previously applied to study this phenomenon, and provides opportunities for further research.